Evaluation of Missed Clinic Visits at an Academic Multi‐Provider Urology Clinic. Issue 6 (November 2018) - Wilson, Bryan J.; Foreman, Jordan; Riley, Julie M.
Abstract : Introduction : In this study we elucidated patient characteristics and reasons for visit associated with missed appointments for patients in a multi‐provider urology clinic. Methods : We retrospectively reviewed characteristics of clinic patient data for 4 urologists at 0.5 FTE (full‐time equivalent) at a single location between March 18, 2014 and March 18, 2015. Data were collected on new and established patients, including age, health insurance status, time of appointment, reason for clinic visit and gender. The reasons for clinic visit were divided into 27 groups. We used chi‐square analysis to evaluate statistical significance (p <0.05) based on expected rates for age, gender, time of appointment, season of appointment, health insurance status, benign vs malignant conditions and new or returning visit. Results : A total of 4, 812 clinic visits were analyzed with 999 missed patient appointments for an overall no‐show rate of 20.76%. There was no statistically significant difference in the rate of attendance based on patient gender, season of appointment, or morning or afternoon appointment. A statistically significant difference was found in no‐show rate between benign and malignant conditions (23.23% vs 8.85%, p <0.01) and whether it was a new or returning patient visit (29.78% vs 16.66%, p <0.01). In addition, there was a statistically significant difference in patients based on insurance status (p <0.01). Patients without insurance had the highest no‐show rate and those with private insurance had the lowest (38.53% vs 16.35%). Conclusions : These data reveal identifiable characteristics associated with missed clinic visits.